2003
DOI: 10.1046/j.1460-9568.2003.02893.x
|View full text |Cite
|
Sign up to set email alerts
|

Highly regionalized distribution of stromal cell‐derived factor‐1/CXCL12 in adult rat brain: constitutive expression in cholinergic, dopaminergic and vasopressinergic neurons

Abstract: The stromal cell-derived factor-1 (SDF-1)/CXCL12 and its receptor CXCR4 are key modulators of immune functions. In the nervous system, SDF-1/CXCL12 is crucial for neuronal guidance in developing brain, intercellular communication and the neuropathogenesis of acquired immunodeficiency syndrome. However, cerebral functions of SDF-1/CXCL12 in adult brain are poorly understood. The understanding of its role in the adult brain needs a detailed neuroanatomical mapping of SDF-1/CXCL12. By dual immunohistochemistry we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
148
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 150 publications
(161 citation statements)
references
References 35 publications
13
148
0
Order By: Relevance
“…It is clear from these studies and the results presented here that although CXCR4 is expressed by neural progenitors in all of these areas its expression is not restricted to these cells. Indeed, it is now clear that the SDF-1/CXCR4 system is widely expressed by neurons throughout the nervous system and possibly by glial elements as well (Banisadr et al, 2002a(Banisadr et al, , 2003Stumm et al, 2002;Tran and Miller, 2003;Dziembowska et al, 2005). The patterns of expression of the other chemokine receptors in the areas we examined are similar, consistent with previous findings that neural progenitor cells express numerous different chemokine receptor types (Peng et al, 2004;Tran et al, 2004;Pluchino et al, 2005).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…It is clear from these studies and the results presented here that although CXCR4 is expressed by neural progenitors in all of these areas its expression is not restricted to these cells. Indeed, it is now clear that the SDF-1/CXCR4 system is widely expressed by neurons throughout the nervous system and possibly by glial elements as well (Banisadr et al, 2002a(Banisadr et al, , 2003Stumm et al, 2002;Tran and Miller, 2003;Dziembowska et al, 2005). The patterns of expression of the other chemokine receptors in the areas we examined are similar, consistent with previous findings that neural progenitor cells express numerous different chemokine receptor types (Peng et al, 2004;Tran et al, 2004;Pluchino et al, 2005).…”
supporting
confidence: 89%
“…20). Banisadr et al, 2003;Cowell and Silverstein, 2003;Tran and Miller, 2003) and their receptors (Banisadr et al, 2002a,b;Stumm et al, 2002;Chalasani et al, 2003;Cowell and Silverstein, 2003;Tran and Miller, 2003;Belmadani et al, 2005) exhibit a widespread and previously unappreciated expression pattern in the central and peripheral nervous systems. This suggests a number of roles for these molecules in the regulation of the nervous system beyond any role they may play in the organization of neuroinflammatory responses.…”
Section: Chemoattractant Effects Of Chemokines On Neural Progenitor Cmentioning
confidence: 99%
“…If we consider the DG as an example, CXCR4 is expressed by the most immature radial glia like stem cells as well as their progeny including rapidly amplifying cells, neuroblasts and immature granule neurons. Furthermore, SDF-1 is also expressed by neuronal cells in the DG (Banisadr et al, 2003;Stumm et al, 2002). The close juxtaposition of SDF-1 and CXCR4 in the adult DG suggests that CXCR4 may be an important regulator of adult neurogenesis in this part of the brain.…”
Section: Adult Stem Cell Developmentmentioning
confidence: 97%
“…administration of two members of CXC chemokines, IL-8/CXCL8 and IP-10/CXCL10, and two members of CC chemokines, MCP-1/CCL2 and RANTES/CCL5, are also effective in decreasing the short-term (2 h) food intake (Plata-Salaman & Borkoski 1994). More recently, we demonstrated by immunohistochemical studies that SDF-1a/CXCL12 is constitutively expressed in melanin-concentrating hormone (MCH)-expressing neurons located in the lateral hypothalamic area (LHA), neurons which are mainly involved in the stimulation of food intake (Banisadr et al 2003). Moreover, it was shown that the SDF-1/CXCL12 receptor, CXCR4, is also within MCH-expressing neurons confirming the hypothesis that SDF-1/ CXCL12 could alter the feeding behavior by acting on its receptor expressed by MCH neurons in the rat LHA.…”
Section: Chemokines and Feedingmentioning
confidence: 99%